Climatic niche shifts in the serpentine soil flora of California. (16th December 2013) - Burge, Dylan O.; Salk, Carl F.; Kühn, Ingolf
Abstract Question Soil properties are known to have a profound effect on the geographic distribution of plants. Unusual soils seem to allow species to occur outside their 'typical' (realized) climatic niche. However, the generality of this pattern, and the mechanisms that drive it, are poorly known. Here, we focus on the tendency for some plant species to occur at unusually low elevations on infertile substrates, especially serpentine soils. We ask whether there is a flora‐wide trend in the state of California toward lower elevations and warmer thermal limits on infertile serpentine soils than on other soils. Location State of California, USA. Methods We used herbarium data from 19 institutions. We only used species collected from both serpentine and non‐serpentine soils. To focus on plant response to recent climate, we discarded records from before 1979. Finally, we discarded records that did not report latitude and longitude. The final data set consisted of 36 045 specimens representing 814 species. Latitude and longitude were used to infer elevation, temperature and soil type. We then developed a simulation modelling approach to test for significant differences in elevational and thermal distribution between serpentine and non‐serpentine soils. Results Serpentine populations are found at lower elevations than non‐serpentine populations, at both the low and high ends of elevation distributions (two tailed t‐test, P < 0.01). This pattern is partially matched by temperature: both high and low temperature data indicate that serpentine populations are limited to less extreme temperatures than non‐serpentine populations (two tailed t‐test, P < 0.01). Conclusions We show that there is a flora‐wide trend toward lower elevation limits on serpentine soils in the state of California. Temperature data suggest a slightly different pattern, with serpentine plants occupying more moderate temperatures. We suggest that this difference may be due to a decoupling of elevation and temperature in some parts of California. Overall, our results are consistent with two mechanisms of plant range limitation: (1) a biotic mechanism at lower elevations (high temperatures), where serpentine provides a refuge from competition; and (2) an abiotic limit at upper elevations (low temperatures), where the effect of cold is exacerbated by the infertility of serpentine.